RANCANG BANGUN SISTEM LAYANAN ADMINISTRASI PERSURATAN SMKN 4 GORONTALO BERDASARKAN FRAMEWORK ITIL V3 DOMAIN SERVICE DESIGN - Refly K. Batalipu; Ghadiza M. Lompad; Natasya P. Daud; Rossa M. Molamahu; Zainab M. Diko; Muhamad Fadel N. Adam (TRANSFORMASI, 2026)
The mail administration service at SMKN 4 Gorontalo still relies on manual processes, resulting in delayed document distribution, difficulty retrieving archives, and a lack of structured monitoring. This study aims to design a mail administration information system (Simpers) using the ITIL V3 framework, specifically the Service Design domain, integrated with the Business Process Improvement (BPI) approach. The research methodology consists of three phases: data collection and field observation, Business Process Analysis and Improvement (covering As-Is BPMN modeling, evaluation, and To-Be process design), and Service Design (covering feature requirements, database design, UI design, and SLA). The results show that Simpers is equipped with integrated features including OCR-based mail input, digital disposition, e-archiving, Telegram notification, and an IT helpdesk with an SLA tiering system (S1–S4). The system eliminates manual bottlenecks identified in the As-Is process and transforms school administrative workflows into a digitalized, accountable, and traceable system Keywords : ITIL V3, Service Design, Mail Administration System, Business Process Improvement,